Some aspects of abelian and nonabelian T-duality and the gauge/gravity correspondence - Araujo, Thiago Rocha [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
In this thesis we study properties of type II supergravity solutions generated by abelian and nonabelian T-duality. Also we determine, through the gauge/gravity conjecture, some aspects of the field theory dual to the supergravity solutions obtained by T-dualization. We consider three distinct types of backgrounds solutions, namely, backgrounds that are dual to confining field theories, backgrounds dual to conformal field theories and those dual to nonrelativistic field theories. We conclude this thesis with an analysis of Wilson loops on backgrounds with nonrelativistic symmetries.

Nessa tese estudamos propriedades de soluções de supergravidade tipo II obtidas através da dualidade T abeliana e não abeliana. Também determinamos, através da conjectura gauge/gravidade, aspectos da teoria de campos dual a essas soluções obtidas por dualidade T. Consideramos três tipos distintos de soluções: duais a teorias de campos que confinam, duais a teoria de campos conformes e duais a teoria de campos não-relativistas. Concluimos essa tese com uma análise dos laços de Wilson em soluções com simetria não relativista.
Alguns aspectos da dualidade T abeliana e não-abeliana e a correspondência gauge/gravidade
Keywords: AdS/CFT; Gauge/gravidade; Gauge/gravity; Supergravity; String theory; Supergravidade; Teoria de cordas